MOTIVASI BELAJAR DAN KECERDASAN INTERPERSONAL TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL SEKOLAH MENENGAH KEJURUAN SWASTA - Masayu Endang Apriyanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
Abstract: The purpose of this study was to determine the effect of learning motivation towards learning achievement in social studies, the influence of interpersonal intelligence students on achievement social studies, and the effect of learning motivation and interpersonal intelligence together on learning achievement IPS, using survey research methods on correlation analysis and regression. Data learning motivation and interpersonal intelligence obtained through the Likert scale questionnaire, while the data's achievements in social studies syllabus is based on social studies class XII SMK. Research was conducted on March 19, 2015 until 20 March 2015. The results showed: 1). There is a very significant influence learning motivation and interpersonal intelligence together the learning achievement of Social Science (IPS), it is evidenced by FH 479.153 and sig.0,000 <0.05. 2) .Terdapat very significant influence learning motivation towards learning achievement of Social Sciences (IPS), it is evidenced by tH 6.079 and sig. 0.000 <0.05. 3). There is a very significant influence on learning achievement interpersonal intelligence Social Science (IPS), it is evidenced by tH 5.622 and sig. 0.000 <0.05. Keywords: Motivation, Interpersonal Intelligence and Learning Achievement IPS.